Association between ratio indexes of body composition phenotypes and metabolic risk in Italian adults. Issue 6 (21st November 2016) - Powell, M.; Lara, J.; Mocciaro, G.; Prado, C. M.; Battezzati, A.; Leone, A.; Tagliabue, A.; de Amicis, R.; Vignati, L.; Bertoli, S.; Siervo, M.
Summary: The ratio between fat mass (FM) and fat‐free mass (FFM) has been used to discriminate individual differences in body composition and improve prediction of metabolic risk. Here, we evaluated whether the use of a visceral adipose tissue‐to‐fat‐free mass index (VAT:FFMI) ratio was a better predictor of metabolic risk than a fat mass index to fat‐free mass index (FMI:FFMI) ratio. This is a cross‐sectional study including 3441 adult participants (age range 18–81; men/women: 977/2464). FM and FFM were measured by bioelectrical impedance analysis and VAT by ultrasonography. A continuous metabolic risk Z score and harmonised international criteria were used to define cumulative metabolic risk and metabolic syndrome (MetS), respectively. Multivariate logistic and linear regression models were used to test associations between body composition indexes and metabolic risk. In unadjusted models, VAT:FFMI was a better predictor of MetS (OR 8.03, 95%CI 6.69–9.65) compared to FMI:FFMI (OR 2.91, 95%CI 2.45–3.46). However, the strength of association of VAT:FFMI and FMI:FFMI became comparable when models were adjusted for age, gender, clinical and sociodemographic factors (OR 4.06, 95%CI 3.31–4.97; OR 4.25, 95%CI 3.42–5.27, respectively). A similar pattern was observed for the association of the two indexes with the metabolic risk Z score (VAT:FFMI: unadjusted b  = 0.69 ± 0.03, adjusted b  = 0.36 ± 0.03; FMI:FFMI: unadjusted b  = 0.28 ± 0.028, adjusted b  = 0.38 ± 0.02). Our results suggest that there is no real advantage in using either VAT:FFMI or FMI:FFMI ratios as a predictor of metabolic risk in adults. However, these results warrant confirmation in longitudinal studies.